ANALISIS TINGKAT AKTIVITAS FISIK SISWA MELALUI MODIFIKASI PERMAINAN DALAM PEMBELAJARAN PJOK - Tria Fauziah Amelia; Azhar Ramadhana Sonjaya; Asep Angga Permadi (Universitas Hamzanwadi, 2026)
The issue of limited facilities and infrastructure in elementary schools often results in low levels of physical activity among students during Physical Education, Sports, and Health (PJOK) classes. This study aims to analyze the effectiveness of PJOK instruction through game modifications in increasing physical activity among elementary school students. The method used was a quasi-experimental study with a pretest-posttest one-group design. The study population was SDN 05 Sukarame, with a sample of 31 third-grade students selected using purposive sampling. The research instrument consisted of a physical activity questionnaire covering frequency, intensity, duration, and enthusiasm. The intervention was administered over 12 sessions through game-based learning. Data analysis utilized descriptive statistics and the Paired Sample T-Test. The results indicated that all aspects of physical activity improved, with the highest increase observed in the enthusiasm aspect, rising from 59.74% to 90.13% (an increase of 30.39%). Overall, the average physical activity score increased significantly with a p-value < 0.001. The conclusion of this study is that game modification is effective in increasing students’ physical activity, particularly in enhancing students’ emotional engagement and enthusiasm in participating in Physical Education (PJOK) lessons at elementary schools with limited facilities.